Effects of Financial Reporting on Financial Performance of Small and Medium Enterprises in Uganda: A Case Kampala City - Isaac Epielu (Uganda Christian University, 2024)
Financial reporting was a crucial factor in the success of Small and Medium Enterprises (SMEs), particularly within Uganda's competitive business environment. This study examined the impact of financial reporting practices on the financial performance of SMEs in Kampala City, Uganda. It focused on how the adoption of financial reporting standards, consistency, and timeliness of reports enhanced business profitability, efficiency, and liquidity. Additionally, the study identified challenges faced by SMEs in financial management and explored the relationship between key financial reporting factors such as consistency, timeliness, cost constraints, and comparability and financial outcomes. The research adopted a descriptive design to collect data from a sample of 30 SMEs in the service and trade sectors, particularly hotels and restaurants, selected from a population of 43 using Yamane's formula. Both quantitative and qualitative approaches were employed, with structured questionnaires serving as the primary data collection tool. Quantitative data were analyzed using SPSS software to generate descriptive and inferential statistics, such as Pearson correlation and regression analysis, to understand the relationship between financial reporting and financial performance. Qualitative data were processed using content analysis to complement the quantitative findings. The study ensured the validity and reliability of its instruments through expert reviews and Cronbach’s alpha. Ethical considerations included informing participants of the research’s academic purpose and obtaining consent. The findings provided valuable insights into improving financial reporting practices among SMEs, guiding policymakers and business owners toward sustainable growth through enhanced transparency, financial literacy, and corporate governance.
Undergraduate research